2022
DOI: 10.1021/acs.chemmater.2c00329
|View full text |Cite
|
Sign up to set email alerts
|

Transverse and Longitudinal Degradations in Ceramic Solid Electrolytes

Abstract: Ceramic solid electrolytes conducting primarily a specific ion but with minuscule electron leakage are used in many electrochemical devices. Their degradation phenomena may be classified into two broad categoriesa slow transverse mode accumulating damage normal to the ionic current direction and a fast longitudinal mode accumulating degradation parallel to the current direction. Examples of the transverse mode include oxygen bubbles on transverse grain boundaries, in-plane electrolyte cracking in solid oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Active fillers are the main conductive medium, and polymers act as a binder for cross‐linking and adhesion. It forms three different ion transport paths in the composite electrolytes [100,101] . Specifically, there are three‐phase conduction mechanisms in the inorganic‐organic composite SSE, including active filler conduction, polymer/filler interface conduction, and polymer (lithium salt) conduction [102] .…”
Section: Strategies Of Polymer‐based Composite Solid‐state‐electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…Active fillers are the main conductive medium, and polymers act as a binder for cross‐linking and adhesion. It forms three different ion transport paths in the composite electrolytes [100,101] . Specifically, there are three‐phase conduction mechanisms in the inorganic‐organic composite SSE, including active filler conduction, polymer/filler interface conduction, and polymer (lithium salt) conduction [102] .…”
Section: Strategies Of Polymer‐based Composite Solid‐state‐electrolytementioning
confidence: 99%
“…It forms three different ion transport paths in the composite electrolytes. [100,101] Specifically, there are three-phase conduction mechanisms in the inorganic-organic composite SSE, including active filler conduction, polymer/filler interface conduction, and polymer (lithium salt) conduction. [102] Therefore, more work focused on improving the ionic conductivity of polymer-based SSEs by incorporating active fillers.…”
Section: Active Ceramic Fillermentioning
confidence: 99%
“…Lastly, it is important to acknowledge the spatial heterogeneity both at the cathode particle level and at the composite electrode level. The heterogeneity depends on many factors such as the spatial distributions of active materials, conductive carbon, binder, and porosity, macroscopic defects in the electrode, the shape and crystallography of cathode particles, and the spatial uniformity of the surface passivation. It affects the transport of Li + and electrons, as well as the local chemical potential of Li 0 . With a large spatial heterogeneity either from cathode processing or after extended cycling, such as detachment of some particles from the electron percolating network or even wholesale detachment of the electrode from the current collector, these particles would be electrically insulated and become electrochemically inactive. What is worse, the charge/discharge current density calculated from the nominal active material loading would only be loaded on the active ones, which is equivalent to a high-rate cycling condition and result in accelerated degradations.…”
Section: Coupled Electrochemomechanical Degradationsmentioning
confidence: 99%
“…Recent research showed that electrocatalysts designed by alloying two or more elements (e.g., transition metals, TM) showed promising enhancement in catalytic activity and durability due to synergistic effects from alloying, such as strain engineering or valence electron exchange. [4,[10][11][12][13][14][15] Nevertheless, the full potential of the alloying approach is still constrained by standard synthesis methods (e.g., wet chemistry and thermal decomposition techniques) due to the thermodynamics rules (e.g., miscibility of the different alloying elements, Mixed transition-metals (TM) based catalysts have shown huge promise for water splitting. Conventional synthesis of nanomaterials is strongly constrained by room-temperature equilibria and Ostwald ripening.…”
Section: Introductionmentioning
confidence: 99%